HIGH-RESOLUTION XANES SPECTRA OF IRON IN MINERALS AND GLASSES: STRUCTURAL INFORMATION FROM THE PRE-EDGE REGION - Galoisy L.; Calas G.; Arrio M.A. (My University, 2001)
High-resolution X-ray Absorption Near-Edge Structure (XANES) spectra of iron allow to take into account the effects of the coordination numbers on the quantification of redox values. Volcanic glasses show split pre-edge features, arising from a bimodal distribution between the relative contributions of ferric and ferrous iron. The chemical shift between these two oxidation states, 2 eV, has been resolved using a 400 Si monochromator. High-resolution pre-edge spectroscopy shows the distribution of ferric and ferrous iron between various coordination states. Ferrous iron is mostly fivefold-coordinated and minority fourfold-coordinated while ferric iron occurs in fourfold and sixfold-coordinated sites. The importance of 6Fe3+ in basaltic glasses may explain the formation of magnetite during glass oxidation. The increase of 4Fe3+ in the more silicic, pantelleritic glass is consistent with the peralkaline character of this glass. The increase of the proportion of tetrahedral Fe3+, accompanied by more covalent Fe3+-O bonds, is consistent with the chemical dependence of redox equilibria in magmatic systems, in which the most differentiated terms correspond to more oxidizing compositions.
Keywords: VOLCANIC GLASS; X-RAY SPECTROSCOPY; REDOX; COORDINATION; IRON